The Application of Literal Meaning in Semantics to Enhance Vocabulary and Sentence Structure in Children's Speaking Skills - Yuni Enjelina Napitupulu; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study aims to examine how the application of literal meaning, as conceptualized in semantic theory, can support the development of children's speaking skills—specifically in enhancing vocabulary acquisition and sentence structure. Recognizing that early language learners often face challenges in selecting appropriate words and constructing grammatically accurate sentences, this research investigates the pedagogical potential of introducing literal meanings in language instruction. Employing a qualitative research design, data were collected through classroom observations and in-depth interviews with primary school teachers. The findings reveal that instructional strategies emphasizing the use of literal meanings help children comprehend vocabulary more clearly and construct more coherent sentences. These results highlight the significant role of semantic-based teaching approaches in improving clarity and linguistic accuracy in early language education.